زهر الرياض في حكم المتوضئ في الحياض: رسالة في حكم الماء المستعمل في الفقه الحنفي لابن الشحنة الصغير (Journal of Academic Research, 2024)
The aim of this research is to identify a manuscript of Hanafi jurisprudence by one of the major scholars of the Hanafi school of thought in the ninth century, on an issue related to the ruling on purification with used water.The research included two sections: the first section: the academic section, the second section: the text of the manuscript.The research concluded by introducing Ibn al-Shihna and producing the text of the manuscript correctly.The researcher recommended studying jurisprudential manuscripts that highlight the role of scholars of different sects in serving Islamic jurisprudence and enriching its movement.
Keywords: son of shihna; used water